2015
DOI: 10.1177/1548051815585853
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Psychological Capital on Mental Health and Substance Abuse

Abstract: In a large body of literature, the construct of psychological capital (PsyCap) has been shown to predict a wide range of work-related behavioral and attitudinal outcomes. Specifically, PsyCap has been related to increased job performance (across various measures of performance and sources of performance ratings), job satisfaction, organi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 79 publications
8
62
0
3
Order By: Relevance
“…We have seen positivity and positive interventions applied in small, medium, and some of the largest organizations across the world, spanning manufacturing, hospitality, franchises, banking, insurance, marketing, healthcare, telecommunications, shipping, aerospace, military, police, sports, oil and gas, education, government, NGOs, and nonprofits, among others. For example, as mentioned earlier, the U.S. Army and Air Force made large investments in developing resilience (Seligman & Matthews 2011), and empirical studies provide preliminary evidence to support the efficacy of these initiatives in building positivity, buffering negativity, and promoting well-being among those serving in stressful and mission-critical roles (Krasikova et al 2015, Schaubroeck et al 2011. Similarly, Harvard Medical School is now exploring PsyCap applications in the context of sportsrelated concussions and athletes' personal conduct with the goal of enhancing their well-being, alleviating psychosomatic symptoms and improving life skills.…”
Section: Practical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have seen positivity and positive interventions applied in small, medium, and some of the largest organizations across the world, spanning manufacturing, hospitality, franchises, banking, insurance, marketing, healthcare, telecommunications, shipping, aerospace, military, police, sports, oil and gas, education, government, NGOs, and nonprofits, among others. For example, as mentioned earlier, the U.S. Army and Air Force made large investments in developing resilience (Seligman & Matthews 2011), and empirical studies provide preliminary evidence to support the efficacy of these initiatives in building positivity, buffering negativity, and promoting well-being among those serving in stressful and mission-critical roles (Krasikova et al 2015, Schaubroeck et al 2011. Similarly, Harvard Medical School is now exploring PsyCap applications in the context of sportsrelated concussions and athletes' personal conduct with the goal of enhancing their well-being, alleviating psychosomatic symptoms and improving life skills.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Similarly, PsyCap predicted satisfaction with one's relationships, as well as objective investment in one's relationships (time spent with family and friends). Krasikova et al (2015) also favorably linked U.S. Army soldiers' PsyCap prior to deployment to post deployment diagnosed mental health issues and substance abuse.…”
Section: Antecedents and Outcomes Of Psychological Capitalmentioning
confidence: 99%
“…In the organizational context, PsyCap has been shown to be positively related to job satisfaction, job engagement, well-being, mental health and employee performance and negatively related to stress, turnover intentions, substance abuse and counterproductive workplace behaviors (Avey, Reichard, Luthans, & Mhatre, 2011;Aybas & Acar, 2017;Krasikova, Lester, & Harms, 2015;Rabenu, Yaniv, & Elizur, 2016). For a review, (see Newman, Ucbasaran, Zhu, & Hirst, 2014) 1.2 Coping with Stress and psychological capital (PsyCap) Three kinds of personal variables are especially important in shaping stress appraisals (and hence coping): goals, beliefs about the self and the world, and finally the individual's personal resources can be tapped in interactions with the environment (Lazarus, 1999).…”
Section: Positive Psychological Capital (Psycap)mentioning
confidence: 99%
“…Several studies have shown positive and negative connections between psychological capital and different work and organisational variables such as job satisfaction (Badran & Youssef-Morgan, 2015;Karatepe & Karadas, 2015;, organisational commitment (Larson & Luthans, 2006), engagement (Avey, Hughes, Norman & Luthans, 2008), efficacy , intention to leave the organisation (Avey, Luthans & Jensen, 2009;Schulz, Luthans & Messersmith, 2014), burnout (Cheung, Tang & Tang, 2011;Dinget al, 2015), and health and welfare in workers (Avey, Wernsing & Mhatre, 2011;Krasikova, Lester & Harms, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In a similar way, found connections between psychological capital and welfare, and that these are mediated by stress and emotions. Finally, Krasikova et al, (2015) conducted a study with 1889 professional soldiers from the US army, and their results showed that, before a military deployment, soldiers with high levels of psychological capital were less likely to be diagnosed with mental illnesses upon their return.…”
Section: Introductionmentioning
confidence: 99%